Isolation of Staphylococcus spp. from hospital wastewater and adjacent community household water: Special focus on their antibiotic resistance - Fatema, Kaniz (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2023.